EFL Teacher's Classroom Management Practices at an Inclusive School - Eka Anastasia Wijaya; Dewa Ayu Eka Agustini; Luh Diah Surya Adnyani (Indonesian Journal of Disability Studies, 2020)
This research aimed at finding out the classroom management practices by an EFL teacher at an inclusive school. There were four major aspects of classroom management as the focus of this research. Those are rules, physical environment, classroom climate, and teacher's role. The subject of this study was an English teacher in class XI MM 2 at SMK Negeri 3 Singaraja. This study was a case study with qualitative research design. The methods of data collection were observation and interview. The findings showed that the classroom management practices by the teacher were successful to be implemented for both the inclusive and regular students. The rules created and communicated by the teacher were effective to develop the students' behaviour and attitude as well as support the learning process. For the physical environment, the teacher provided spacious space for the physical disability student to move freely. The teacher gave positive and negative reinforcements for the students' attitude and behaviour. Besides, the teacher modified the lesson plan, instruction, and assessment based on the student's special needs. However, the teacher did not interact directly with the inclusive student's parents and it should be done to support the learning process. In addition, there was no special escort teacher and training for the teacher to support the learning process.